Community voices on climate, peace and security: a social learning approach - Medina, Leonardo; Pacillo, Grazia; Hellin, Jonathan James; Bonatti, Michelle (2023)
The Climate Security Observatory (CSO) is an online platform for stakeholder decision-making that provides access to a range of global analyses related to climate and security. The CSO is based on an integrated climate security framework that helps understand the complexity of the climate-security interface. As part of the CSO methods paper series, this report details the social learning theory approach used to analyse community voices on climate, peace and security.